A expansão das commodities e a suposta desindustrialização na região nordeste do Brasil no período 1991-2012 - Souza, Kamille Leão de (2013)
Nowadays deindustrialization underway in economies that have not yet reached a high per capita income is the main theme in debates. Several studies were conducted to Brazil on this subject, but the Northeast still lacks analysis in this area. The central hypothesis of this study is to verify ig the Northeast economy was deindustrialized in the period 1991-2012, from the continued growth of commodities in totalexports couopled with the highest share of products with higher technological content in the imports. The analysis was carried out by using data on the trade balance, exports and imports, registering the share of commodities and industrial products, according to the classification adopted by OECD and MDI C (high, medium-high, medium-low, low-tech and unprocessed products), the value added by industry, the share of manufacturing employment and total income (GDP). To this end, we calculated indicators foreign trade (Export Concentration Index-ICX, Concentration Index of Import-ICM, Revealed Comparative Advantage Index over the trade balance-VCR, simple rate of coverage of imports and TC-Index of intra-industrytrade-CII and an econometric model was regressed to verify traces of deindustrialization in relation to industrial production. The results indicate that the northeast export tariff undergoes a reprimarization that, when associated with the increased presence of industrial products with higher technological content of imports, show signs of deindustrialization. However, it is not possible to come to the conclusion that the northeast economy suffers the dutch disease because signs of loss of importance on the industrial sector in total did not appear on the analysis of industrial employment and of the value added by industry in the totaleconomy. There, such results corroborated with the econometric model regressed. However, some industries (textile, clothing and accessories and machinery, equipment and material) showed a decreasing trend in the evolution of the physical industry production index, which may indicate a kind of loss.